2017
DOI: 10.17116/kurort201794459-66
|View full text |Cite
|
Sign up to set email alerts
|

What physiotherapeutic method for the treatment of post-mastectomy lymphedema is the most effective?

Abstract: We have undertaken the search for the publications of interest in the following databases: Scopus, Web of Science, MedLine, The Cochrane Library, CyberLeninka, and Russian science citation index. In addition, we evaluated the effectiveness of the physical agents and procedures having different mechanisms of action of the known factors responsible for the development of post-mastectomy lymphedema. Such agents and procedures include self-massage, manual lymphatic drainage, therapeutic physical exercises, compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(12 reference statements)
0
2
0
1
Order By: Relevance
“…In the secondary criteria, 8 groups contain quality of life, but the evaluation criteria are different, including EQ-5D questionnaire [7], LYMQOL arm questionnaire [8], validated questionnaire [6], QLQ-BR23 questionnaires [9], four questions [10], visual analogue scale [11], the Lymphedema Questionnaire [5]. There are 2 group that involve compliance [9] [8], the evaluation criteria is EORTC QLQ-C30 questionnaires [9].…”
Section: Results Subsectionmentioning
confidence: 99%
“…In the secondary criteria, 8 groups contain quality of life, but the evaluation criteria are different, including EQ-5D questionnaire [7], LYMQOL arm questionnaire [8], validated questionnaire [6], QLQ-BR23 questionnaires [9], four questions [10], visual analogue scale [11], the Lymphedema Questionnaire [5]. There are 2 group that involve compliance [9] [8], the evaluation criteria is EORTC QLQ-C30 questionnaires [9].…”
Section: Results Subsectionmentioning
confidence: 99%
“…Although recent studies have not shown superiority over one another, combined therapies in advanced stage lymphedema are recommended ( 23 , 24 , 25 , 26 , 27 ) . There are serious developments in alternative and new surgical approaches in the management of lymphedema ( 28 ) . Methods such as physical activity, acupuncture, healing touch, hypnosis, and music therapy, yoga, tai chi, visual reality, and cognitive behavior therapy are also used in cancer pain ( 29 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Elektrik stimülasyonu Elektrik akımları, kas kasılmasını arttırmak, kan akımını arttırmak, ağrıyı azaltmak, ödem azaltmak ve doku iyileşmesini hızlandırmak amaçlarıyla kullanılmaktadır (1,35).…”
Section: Fizik Tedavi Modaliteleriunclassified